The Grand Escape - Naylor, Phyllis Reynolds; Daniel, Alan (New York, 1993)
After years of being strictly house cats, Marco and Polo escape into the wonderful, but dangerous outside world and are sent on three challenging adventures by a group of cats known as the Club of Mysteries.
Keywords: Cats; Fiction; Adventure and adventurers; Fiction